Gain control in S-band erbium-doped fiber amplifier using a fiber bragg grating - Harun, Sulaiman Wadi; Saat, Nor Kamilah; Ahmad, Harith (2005)
A gain-clamped short wavelength band erbium-doped fiber amplifier (S-band EDFA) is demonstrated utilizing a fiber Bragg grating (FBG). The amplification in S-band is achieved using an erbium-doped fiber (EDF) with depressed cladding design, which suppressed amplified spontaneous emission (ASE) at longer wavelength. The gain clamping is achieved by routing back the forward ASE into the feedback loop as to create a ring laser. The clamped gain is controlled using a variable optical attenuator (VOA) as to generate a gain of 14.6 to 25.2 dB for input signal at 1504 nm. At VOA = 0 dB, the gain is clamped at 14.6 dB with a gain variation of less than +/- 0.5 dB for input signal at 1504 nm with power dynamic range of - 40 to - 5 dBm. The noise figure penalty is less than 0.8 dB in this amplifier since the laser is arranged to be co-propagated with the signal.